Impact of ethanol plants on Kansas land values - Cretin, Curtis J. (Kansas State University, 2015)
Land values have a fascinating history after the first settlers started moving west in the 19th century. Much research has been done in agricultural economics with regards to land values and this subject will continue to be watched closely as we move further into the 21st century. The goal of this thesis is to understand the effect that ethanol plants have on the price of land around the ethanol plant. More specifically, the thesis addresses the question of “What impact do ethanol plants have on Kansas Land values?” The thesis also answers the question of “Are land values directly correlated to the proximity of an ethanol plant and if they are directly correlated, to what extent or how much more valuable is a parcel of land that is 30 miles to an ethanol plant compared to a parcel of land that is 70 miles?” As we move into the 21st century, the nation continues to look for alternative fuel sources. Ethanol produced from corn has played a key role in that search for an alternative fuel. In 2007, the state of Kansas proposed to have 29 ethanol plants built and/or operational in the near future. The majority of the ethanol plants were built in 2006 and 2007 with only 16 of those plants becoming operational. This thesis uses those 16 ethanol plants as the basis of this study. The study determines if land sale values from 2010 to 2013 were directly impacted based on the proximity to the closest ethanol plant. Corn is the main crop used in this study with regards to the production of ethanol. While other crops can be used to produce ethanol, the study only focused on the corn crops from 2010 to 2013. The trend in cash corn prices and basis data reflects the advent of the development of ethanol plants with a cash corn high of $8.05 in 2012 and a basis high of $1.84 above futures prices in 2013. In addition to cash corn prices and basis data, the study also collected land parcel sales from the years 2010 to 2013 with 9,279 total observations. Utilizing regression, an equation was estimated taking into account land price, size of land parcel sold in acres, quarter of year for sale, a year binary variable, the minimum distance of an ethanol plant to each parcel sale, the percent pasture acres, percent irrigation acres, rainfall, cropland productivity, and population density. Results indicated that land closer to an ethanol plant is priced at a premium compared to land further away. Land values will continue to be closely studied as we move into the 21st century. This study was able to provide a price point per mile of how much more valuable a land parcel is the closer it is located to an ethanol plant. While this study only factored in the closest ethanol plant to that land parcel sale, other factors such as including multiple ethanol plants located in the same town or ethanol plants that are close in proximity to each other could be further analyzed to continue research on this topic.
Keywords: Land Values; Ethanol Plants; Rainfall; Productivity; Population Density; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Finance (0508)